Использование методов Data Mining при анализе социальных явлений - Шуба, Ирина Владимировна (Харківський національний університет Повітряних Сил імені Івана Кожедуба, 2014)
В статье проанализирована возможность применения интеллектуальных методов обработки данных при анализе социальных явлений. Приведен пример обработки данных анкет студентов пятого курса различных специальностей, используя аналитическую платформу Deductor. Были выявлены факторы,оказывающие влияние на «удовлетворенность» выбранной специальностью пятикурсников.

In the article possibility of application of intellectual methods of processing of data is analysed at the analysis of the social phenomena. The example of treatment of these questionnaires ofstudents of fifth course of different specialities is resulted, using the analytical platform of Deductor. Factors were exposed having influence on «satisfaction» by the chosen speciality of 5-years education.
Usе of methods of Data Mining is for analysis of the social phenomena
Keywords: интеллектуальные методы анализа данных; нейронная сеть; самоорганизующиеся карты Кохонена; прогнозирование; intellectual methods of analysis of data; neuron network; selfgettings organized karty Kokhonena; prognostication